In the name of Perón. The political use of the past in Unidos magazine (1983-1991) (Quinto Sol, 2012)
Unidos magazine was published between 1983 and 1991 by a group of peronist militants and directed by Carlos “Chacho” Álvarez. Its aim was to reinstall peronism in the context of the “return to democracy”. In this way, the magazine made a particular use of the past, more specifically of the peronist experience of 1973-1974 (the last Perón), to intervene politically in the eighties. Unidos constructed a democratic, pluralist and frentist peronist past which carried Peron’s mark on one hand, while it recognized Alfonsín’s democratic values on the other hand. This particular use of the past allowed Unidos to support the rising of the Peronist Renewall, to dispute with alfonsinists the senses of democracy, to oppose menemism and to end up supporting the “group of the eight” justicialist deputies against Menem. These choices were determined by the images that the magazine members created about peronism and Peron´s legacy, and the ones that made Unidos call to abandon the justicialist party and build new political identities, as the only way of being loyal to this peronist past.
Keywords: Unidos magazine; Peronist Renewal; past; Perón; Montoneros